Activating frataxin expression by single-stranded siRNAs targeting the GAA repeat expansion. Issue 17 (15th September 2018) - Shen, Xiulong; Kilikevicius, Audrius; O'Reilly, Daniel; Prakash, Thazha P.; Damha, Masad J.; Rigo, Frank; Corey, David R.
Graphical abstract: Highlights: Frataxin expression can be activated by single-stranded RNAs. Activation can be achieved in multiple patient-derived cell lines. ss-siRNAs are a new starting point for therapeutic discovery. Abstract: Friedreich's ataxia (FRDA) is an incurable neurodegenerative disorder caused by reduced expression of the mitochondrial protein frataxin (FXN). The genetic cause of the disease is an expanded GAA repeat within the FXN gene. Agents that increase expression of FXN protein are a potential approach to therapy. We previously described anti-trinucleotide GAA duplex RNAs (dsRNAs) and antisense oligonucleotides (ASOs) that activate FXN protein expression in multiple patient derived cell lines. Here we test two distinct series of compounds for their ability to increase FXN expression. ASOs with butane linkers showed low potency, which is consistent with the low Tm values and suggesting that flexible conformation impairs activity. By contrast, single-stranded siRNAs (ss-siRNAs) that combine the strengths of dsRNA and ASO approaches had nanomolar potencies. ss-siRNAs provide an additional option for developing nucleic acid therapeutics to treat FRDA.